New aspects in bis and tris(dipyrrinato)metal complexes: bright luminescence, self-assembled nanoarchitectures, and materials applications. Issue 30 (14th August 2015) - Sakamoto, Ryota; Iwashima, Toshiki; Tsuchiya, Mizuho; Toyoda, Ryojun; Matsuoka, Ryota; Kögel, Julius F.; Kusaka, Shinpei; Hoshiko, Ken; Yagi, Toshiki; Nagayama, Tatsuhiro; Nishihara, Hiroshi
<x xml:space="preserve">Abstract</x> This review summarizes recent progress in bis and tris(dipyrrinato)metal complexes, focusing on luminescence intensification, supramolecules and nanostructures, and materials applications.